Analisis Pembelajaran Berbasis Digital pada Era Disrupsi 4.0 di Kelas V SD IT Samawi Bantul - Erizal Afif Fadilah; Riska Anintyawati (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
This study aims to describe the analysis of the implementation of digital-based learning in the era of disruption in class V SD IT Samawi, Bantul. The research method used is descriptive qualitative. Data collection techniques include observation, interviews and documentation. The informants in this study consisted of a class V teacher Ar-Rozy, a class V teacher Ibnu-Rusyd, one class V Ar-Rozy student, one class student Ibnu-Rusyd and the vice principal of the curriculum division. Observations were made to observe the planning, implementation and evaluation of digital-based learning. The documentation needed is vision and mission, interview transcripts and brief biodata of the informants. The results of research in the field show that digital-based learning in class V is running quite well. Students and teachers are able to operate digital media used in the course of learning. In digital-ased learning the teacher has planned and implemented using media, learning methods and approaches that are adapted to the abilities of students. Digital-based learning is able to encourage teachers to be more creative in carrying out learning. In addition, students are required to be more independent and motivated in carrying out digital-based learning. However, in the implementation of digital-based learning there are obstacles to students who need special guidance because there are some students who are not used to operating digital media used in learning.